Livelihood Assets Analysis of Freshwater Stingray Fishermen in Musi River, Palembang City, South Sumatera - Septiani, Nabila Nur; Wijayanti, Pini; Azzahra, Sahaya Aulia; Nikmah, Lailatun (Faculty of Fisheries and Marine Science, Brawijaya University, 2024)
Freshwater stingrays play a crucial role in the ecological and economic functions of the Musi River. Their existence in the Musi River is threatened by both natural and human factors. The livelihoods of fishermen in the Musi River depends on the sale of freshwater stingrays. This study aims to analyze the livelihood assets of freshwater stingray fishermen and their relation to natural, human, financial, physical, and social aspects. The research was conducted from February 2023 to March 2023 in the district of Seberang Ulu II, Plaju, Kertapati, and Gandus in Palembang City, South Sumatra Province. Livelihood asset analysis was performed using the livelihood asset method. The results indicate that the livelihood assets of fishermen in these districts have a moderate sustainability status, ranging from 0.48 to 0.50. Physical and natural assets have the lowest sustainability status index, averaging 0.31 across the four districts. Social assets in the four districts have the highest sustainability status index, averaging 0.88. These scores demonstrate the dependence of fishermen's livelihoods on the assets they possess. Recommendations from this study include the need to enhance financial and capital assets to reduce the sale of freshwater stingrays.